The Long Timeline of the Ice: A Geological Perspective on the Arctic Ocean - Jakobsson, Martin (Journal of Northern Studies, 2021)
Ice ages constitute a significant part of Earth’s climate history with the first signs of widespread ice sheets occurring at about 2.4 billion years ago. In 2004, a nearly 450 metres thick accumulation of seafloor sediments on the submarine Lomonosov Ridge in central Arctic Ocean was drilled by the international Arctic Coring Expedition (ACEX). This geological archive has provided insights into the long-term history of the Arctic Ocean back to 56 million years. The first signs of extensive sea ice along the Arctic coasts appear 47.5 million years ago (Ma), while evidence for the type of pack ice we have today that survives more than one season occurs first 15–13 Ma. The Earth’s climate changed mode at about 2.6 Ma. Cold periods, characterized by large ice sheets covering the Northern Hemisphere, were intervened by warmer periods with climates more similar of today. These glacial-interglacial cycles were largely controlled by changes in solar insolation resulting from cyclical variations in Earth’s orbit around the Sun. In this article, I tell the personal story of how we mapped the Lomonosov Ridge and found evidence supporting a controversial hypothesis of the existence of kilometre-thick floating ice shelves in the Arctic Ocean during past glaciations.